Of hearts and minds Filipino adult viewers' message interpretation processing of vaccination-related public service announcements - Flores, Jaime Manuel Q. (2010)
This study aims to find out how Filipino adult viewers interpret vaccination-related public service announcements (PSAs), using the Message Interpretation Processing (MIP) framework by Austin, et al. (2001). Specifically, the study targets to: 1) determine the interpretation process used by viewers (logic-based or emotion-based); and 2) identify influential factors in relation to these interpretation processes. Data was acquired from 174 walk-in patients of three randomly selected barangay health centers in Paranaque City. Respondents answered a survey questionnaire after viewing three PSAs on rabies, polio and measles. Data were analyzed using correlation analysis and multivariate regression analysis. The study revealed that most viewers tend to interpret vaccination-related PSAs more logically than emotionally. Results also showed that logic-based interpretation is highly influenced by outcome expectancies, while emotion-based message interpretation processing is highly influenced by viewers? close identification with PSA portrayals.